2017
DOI: 10.1021/acs.biomac.7b00023
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine-Modified Hydroxyethyl Starch as a Polymeric Drug for Cancer Therapy

Abstract: Hydroxyethyl starch (HES) is a clinically used polysaccharide colloidal plasma volume expander. The goal of this study was to synthesize HES modified with hydroxychloroquine (HCQ) as a novel polymeric drug with the ability to inhibit the invasive character of pancreatic cancer (PC) cells. HES was conjugated with HCQ using a simple carbonyldiimidazole coupling to prepare Chloroquine-modified HES (CQ-HES). CQ-HES with various degrees of HCQ substitution were synthesized and characterized. Atomic force microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…33 Furthermore, many studies have already focused on using autophagy inhibitors like CQ or hydroxyl-chloroquine (HCQ) as a potential sensitizer for cancer therapy. [34][35][36] However, clinical data have proved that the nonspecific characteristics of these drugs inevitably lead to the treatment toxicity and side effects, which limits their clinical application to some extent. 37 In recent years, the role of CTSD in autophagy and its application in clinics have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, many studies have already focused on using autophagy inhibitors like CQ or hydroxyl-chloroquine (HCQ) as a potential sensitizer for cancer therapy. [34][35][36] However, clinical data have proved that the nonspecific characteristics of these drugs inevitably lead to the treatment toxicity and side effects, which limits their clinical application to some extent. 37 In recent years, the role of CTSD in autophagy and its application in clinics have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…To retain the branched structure of amylopectin, hydrodynamic diameters around dozens of nanometers have been frequently measured in HES solutions with DLS. 28,34,58,59,76 TEM and AFM imaging has revealed that HES exhibits a colloidal structure in self-assembled nanoparticles 67,77 and conjugates. 60 Nonetheless, the conformation and structure of a single HES particle remains an enigma.…”
Section: Resultsmentioning
confidence: 99%
“…The size distributions of HES in an aqueous solution have been reported in previous studies. 34,76,77 However, the morphology of HES is largely unknown, particularly that of a single HES particle. TEM and AFM have been widely employed to directly characterize the morphology of macromolecules.…”
Section: Hes Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides HPMA‐based PCQ, our group reported another PCQ drug, chloroquine‐modified hydroxyethyl starch (CQ‐HES) which was synthesized by conjugation of HES with HCQ by a carbonyldiimidazole coupling. CQ‐HES was able to target CXCR4 signaling and improve inhibition of migration and invasion of PC cells when compared with HCQ (Sleightholm, Yang, Yu, Xie, & Oupický, ). Overall, PCQ represents a new generation of safe and effective CXCR4 inhibitors for metastatic cancer therapy.…”
Section: Chloroquine‐based Cxcr4 Antagonists (Pcq)mentioning
confidence: 99%